Long-term nitrogen fertilization alters microbial respiration sensitivity to temperature and moisture, potentially enhancing soil carbon retention in a boreal Scots pine forest - Ťupek, Boris; Lehtonen, Aleksi; Manzoni, Stefano; Bruni, Elisa; Baldrian, Petr; Richy, Etienne; Adamczyk, Bartosz; Guenet, Bertrand; Mäkipää, Raisa (Copernicus Publications, 2025)
Nutrient availability affects microbial respiration kinetics; their sensitivities to environmental conditions; and, thus, the soil organic carbon (SOC) stocks. We examined long-term nitrogen (N) addition effects on soil heterotrophic respiration (Rh), methane (CH4) oxidation, and nitrous oxide (N2O) emissions in an N-limited boreal Scots pine (Pinus sylvestris) forest in central Finland. Measurements included the following (in both control and N-fertilized plots): longterm tree biomass monitoring (1960–2020); soil organic carbon (SOC) monitoring in 2023; monthly aboveground litterfall monitoring (2021–2023); biweekly CO2, CH4, and N2O fluxes during the 2021–2023 growing seasons; and quarterhourly recordings of soil temperature (T ) and soil water content (SWC). We assessed mean greenhouse gas (GHG) flux differences and Rh dependence on T and SWC using polynomial and nonlinear regression models. Tree biomass, litterfall, and SOC increased with long-term N fertilization. However, N fertilization also significantly increased mean Rh, reduced CH4 oxidation slightly, and modestly raised N2O emissions. SOC-normalized Rh (Rh/SOC) did not significantly differ between treatments, yet relationships between Rh/SOC and T and SWC diverged with fertilization. In control plots, Rh/SOC peaked at 15.8°C, whereas it peaked at 16.8°C in N-fertilized plots. Under N fertilization conditions, Rh/SOC was weakly SWC-dependent, contrasting with a distinct humped SWC response enhancing annual Rh/SOC in control plots. Annually, N-fertilized plots respired 10.3% of SOC (±0.3SE, standard error), compared to 12.2% ( ±0.5SE) in control plots, suggesting that N fertilization promoted SOC retention. Consequently, N fertilization reduced average annual net CO2 emissions by 345.4 ( ±73.6SE)gCO2m-2yr-1, while the combined effects on CH4 and N2O fluxes and the production energy of N fertilizer contributed a minor CO2-equivalent increase of 17.7 (±0.5SE)gCO2eq.m-2yr-1. In conclusion, long-term N fertilization in boreal forests could reduce the global warming potential of soil GHG emissions, mainly by slowing Rh/SOC and altering its responses to T and SWC, thereby enhancing SOC sequestration in addition to the increased tree biomass carbon sink.
Keywords: forests; Scots pine; nitrogen fertilization; soil carbon